Frames in American TV discussions - Nowicka, Agnieszka (Editura Universităţii de Vest Timişoara, 2010)
The paper focuses on analyzing the role of frames in American TV discussions in conversation analysis framework. The analysis aims at creating a tentative classification of frame types depending on their interactive positioning in discussions and their meaning as perceived in participants’ perspective. Observation of two discussion types shows that interactants’ orientation to the type of the communicative event can influence the use of frames.
Keywords: Ethnomethodological conversation analysis; Meta-formulations; Reformulations; TV discussions